Consumer studies educators' digital technology use: a case in North West, South Africa - Du Toit, A.; Goosen, L (Journal of Consumer Sciences, 2024)
Digital technologies can significantly promote education and will especially benefit current school learners who are digital natives, preparing them for life and the world of work. Increasingly, research reports how digital technologies support education in various school subjects. However, no such research could be uncovered for Consumer Studies (CS) - a valuable and meaningful South African school subject. As CS teachers have repeatedly reported a dearth of resources to foster education in the subject, digital technologies could contribute to ameliorating this problem. The purpose of this paper is, therefore, to report on a study that explored CS teachers' use of digital technologies to support teaching-learning in this valuable subject. The objectives of the research were to understand if and how CS teachers are utilising digital technologies for teachinglearning purposes and to develop recommendations for enhancing its use to buttress CS education in South Africa. An exploratory qualitative case study was conducted using purposive convenience sampling in the North West province. Twenty CS teachers completed an online questionnaire. The data were inductively analysed. Although findings indicate that several CS teachers embrace digital technologies, it is done with a limited range of educational intentions and teachers need more guidance in this regard.